The potential role of the orexin system in premenstrual syndrome - Dong, Ping; Dai, Weibo; Su, Mengyue; Wang, Shukun; Ma, Yuexiang; Zhao, Tingting; Zheng, Feng; Sun, Peng (Frontiers in Endocrinology, 2024)
Premenstrual syndrome (PMS) occurs recurrently during the luteal phase of a woman's menstrual cycle and disappears after menstruation ends. It is characterized by abnormal changes in both the 2 body and mood, and in certain cases, severe disruptions in daily life and even suicidal tendencies.Current drugs for treating PMS, such as selective serotonin reuptake inhibitors, do not yield satisfactory results. Orexin, a neuropeptide produced in the lateral hypothalamus, is garnering attention in the treatment of neurological disorders and is believed to modulate the symptoms of PMS.This paper reviews the advancements in research on sleep disturbances, mood changes, and cognitive impairment caused by PMS, and suggests potential pathways for orexin to address these symptoms.Furthermore, it delves into the role of orexin in the molecular mechanisms underlying PMS. Orexin regulates steroid hormones, and the cyclic fluctuations of estrogen and progesterone play a crucial role in the pathogenesis of PMS. Additionally, orexin also modulates the gamma-aminobutyric acid (GABA) system and the inflammatory response involved in coordinating the mechanism of PMS.Unraveling the role of orexin in the pathogenesis of PMS will not only aid in understanding the etiology of PMS but also hold implications for orexin as a novel target for treating PMS.